Controlled synthesis of thermosensitive tunable porous film of (pNIPAM)‐b‐(PCL) copolymer for sustain drug delivery. Issue 20 (9th March 2023) - Amgoth, Chander; Patra, Sukanya; Wasnik, Kirti; Maity, Pradip; Paik, Pradip
Abstract: There have been reports on different types of porous polymer films for various applications. The designing of such porous films with uniform properties is a challenging task. In this work, tunable porous thin films of poly(N‐isopropylacrylamide) (pNIPAM) and polycaprolactone (PCL), that is, (pNIPAM)‐ b ‐(PCL) has been fabricated and its sustained drug delivery applications have been reported. First, the (pNIPAM)‐ b ‐(PCL) has been synthesized through the addition polymerization of pNIPAM and PCL. Then the synthesized (pNIPAM)‐ b ‐(PCL) has been used to design porous thin film with varying temperatures without using any external template, below and above the lower critical solution temperatures (LCST) of pNIPAM. Pore size in (pNIPAM)‐ b ‐(PCL) films has been tuned by varying the temperature from ~10 to 40°C. Then the developed thermosensitive porous film has been taken and seeded with the K562 (chronic myeloid leukemia blood cancer) and HepG2 (hepatocarcinoma) cells and the skin cancer cells (B16‐F10) killing efficiency of anticancer drug (e.g., doxorubicin hydrochloride, DOX) loaded (pNIPAM)‐ b ‐(PCL) film has been studied. It is found that the DOX‐loaded (pNIPAM)‐ b ‐(PCL) can efficiently kill the skin cancer cells. The porous polymer thin film reported in this work can be a versatile platform for the loading of drugs and it can be used for the various therapeutic applications. Abstract : Thermosensitive tunable porous film of (pNIPAM)‐ b ‐(PCL) for sustain drug delivery.